POPULATION DYNAMICS AND SUSTAINABLE ECONOMIC GROWTH IN INDIA - Dr. Ankita Kumari (International Educational Journal of Science and Engineering, 2025)
This research paper provides a comprehensive analysis of India’s population growth and its impact on economic development, focusing on demographic trends, economic indicators, theoretical frameworks, and policy implications. It delves into historical population growth patterns, current demographic trends, and regional disparities, offering insights into India’s unique challenges and successes. The study explores the relationship between population growth and economic sectors, emphasizing agriculture, industry, and services. Theoretical frameworks, including the demographic transition theory and economic development theories, are discussed with relevance to India’s context. The paper presents case studies of states such as Kerala, Tamil Nadu, Himachal Pradesh, Maharashtra, and West Bengal, showcasing successful strategies in managing population growth and achieving sustainable economic development. Policy implications highlight the importance of family planning, women’s empowerment, education, and healthcare initiatives. The research contributes to the understanding of population dynamics and economic progress, providing valuable insights for policymakers and researchers.